Modelling of property market: the structural and locational attributes towards Malaysian properties. (1st September 2016) - Kam, Kenn Jhun; Chuah, Shi Yi; Lim, Tze Shwan; Lin Ang, Fuey
Abstract: House acts as a basic shelter icon for all mankind. In recent years, property value has never stopped receiving attention in the market and has remained the topic of discussion and research on reputable property platforms and all around the world. Residential properties in Malaysia experienced significant appreciation in recent years and this creates anxiety among people. The real factors behind the tremendous rise of property prices in Malaysia however, are yet to be discovered. Structural and locational attributes are frequently discussed and have received uncountable attentions from the whole nation. This study intends to ascertain the factors affecting the property prices. The area of study comprised double storey terrace houses in Mukim Rawang, Selangor, Malaysia. Documentary analysis is conducted in this research with the real transaction data collected from JPPH. Using the regression analysis, various factors were included in the models to capture the particular effects on property values. In particular, built-up area is the most significant structural attribute; whereas shopping centre is the most significant locational attribute in determining the property prices. This paper serves as a guide for the developers and house buyers in decision-making for development and investments.